2008
DOI: 10.1088/0256-307x/25/7/095
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Analysis of Composition and Depth Profile of H in Amorphous Si 1− x C x :H Films

Abstract: Composition in amorphous Si1−xCx:H heteroepitaxial thin films on Si (100) by plasma enhanced chemical vapour deposition (PECVD) is analysed. The unknown x (0.45-0.57) and the depth profile of hydrogen in the thin films are characterized by Rutherford backscattering spectrum (RBS), resonance-nuclear reaction analysis (R-NRA) and elastic recoil detection (ERD), respectively. In addition, the depth profile of hydrogen in the unannealed thin films is compared to that of the annealed thin films with rapid thermal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…As a result, in terms of Eq. (1) with Λ ∝ α −6 , the cosmological constant term should be time and space-dependent too [21,[25][26][27][28][29]. In this case, it might be responsible for the possible anisotropy in the accelerated expansion of the universe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, in terms of Eq. (1) with Λ ∝ α −6 , the cosmological constant term should be time and space-dependent too [21,[25][26][27][28][29]. In this case, it might be responsible for the possible anisotropy in the accelerated expansion of the universe.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a time-varying fine structure constant α has been extensively discussed in the literature [25][26][27][28][29]. In this scenario, α is only time-dependent and increasing with time [21,22,30].…”
Section: Introductionmentioning
confidence: 99%
“…The excitation of SPs in metal nanostructures can enable the manipulation of light intensity [3][4][5], polarization [6,7] and propagation [8,9] at the nanoscale. Therefore, SPs provide the possibility to miniaturize optical devices to the scale compatible with modern nanoelectronic devices [10] and to build highly integrated nanophotonic circuits [11,12]. Plasmonic waveguides are the most basic elements for constructing such nanophotonic circuitry.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic waveguides are the most basic elements for constructing such nanophotonic circuitry. Among the various structures for plasmonic waveguides, chemically synthesized crystalline silver nanowires show low scattering loss for the waveguiding and are widely used in the study of nanowire SP properties [13][14][15][16][17][18][19][20][21], the interaction between propagating SPs and quantum emitters [22][23][24][25][26][27], and the coupling between plasmonic and photonic waveguides [28][29][30]. These wires can support different SP modes with special near-field distributions which have been revealed by fluorescence-based near-field imaging technique [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional material systems with perpendicular magnetic anisotropy (PMA) include rare-earth/transition-metal alloys [1,2], L1 0 -ordered Co (or Fe)-Pt alloys [3][4][5], and Co (or CoFe)-based multilayers [6][7][8]. However, low tunneling magnetoresistance (TMR), and large switching current density were observed in MTJs using these materials as ferromagnetic electrodes due to their low spin polarization (SP), large damping constant and poor lattice matching with an MgO barrier [9][10][11]. It was reported that PMA could be observed at Co(Fe)/oxide interfaces induced by the hybridization between Co (Fe) 3d and O 2p orbitals [12,13].…”
mentioning
confidence: 99%